Pricing farmer contributions under AIP - Banda, Chimwemwe; De Weerdt, Joachim; Duchoslav, Jan; Jolex, Aubrey (International Food Policy Research Institute, 2022)
The market price of fertilizer in Malawi has, in nominal terms, more than tripled compared to two years ago. The price hikes were both unexpected and beyond the control of the government, linked to global events, such as the COVID-19 pandemic and Russia’s invasion of Ukraine. This changed global reality reinforces the need to rethink the way in which Malawi approaches its agricultural input subsidies. A number of options for reforming the AIP have been outlined in recent policy work, but all have medium to long term implementation horizons. We will not repeat these here and instead refer the interested reader to Chadza and Duchoslav (2022), De Weerdt and Duchoslav (2022), and Nyondo et al. (2022). This policy note discusses a strategy that can be implemented readily and immediately, potentially still this year, to ensure that the budget allocated to fertilizer subsidies has the highest possible effect on food security in the country. It also discusses how the strategy, once adopted, can be used to phase out the AIP, while ensuring allocative efficiency within the program. This can be achieved by, each year, fixing the budget at a lower point and conducting the same optimization exercise.